2008
DOI: 10.1016/j.bandc.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Preserved metamemorial ability in patients with mild Alzheimer’s disease: Shifting response bias

Abstract: Patients with mild Alzheimer's disease (AD) display a greater tendency to endorse unstudied items as 'old' on memory tests than healthy older adults. This liberal response bias may result in mistaken beliefs about the completion of common tasks. This research attempted to determine whether it was possible to shift the response bias of mild AD patients to be more conservative on a recognition memory test through behavioral intervention. Patients with mild AD and matched controls were evaluated with two almost i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Several studies examining meta-memory have found evidence that patients perform similar to healthy controls on tasks measuring meta-memory (Bäckman & Lipinska, 1993; Gallo, Cramer, Wong, & Bennett, 2012; Moulin, Perfect, & Jones, 2000; Schmitter-Edgecombe & Seelye, 2011). As reviewed previously, Waring et al (2008) found that patients could shift their response bias when given more detailed instructions about the memory test. However, in the current study, patients were not told to respond in any specific manner.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Several studies examining meta-memory have found evidence that patients perform similar to healthy controls on tasks measuring meta-memory (Bäckman & Lipinska, 1993; Gallo, Cramer, Wong, & Bennett, 2012; Moulin, Perfect, & Jones, 2000; Schmitter-Edgecombe & Seelye, 2011). As reviewed previously, Waring et al (2008) found that patients could shift their response bias when given more detailed instructions about the memory test. However, in the current study, patients were not told to respond in any specific manner.…”
Section: Discussionmentioning
confidence: 64%
“…Given that many studies have found an abnormally liberal response bias in patients with AD despite different experimental stimuli and conditions (Beth, Budson, Waring, & Ally, 2009; Budson, Wolk, Chong, & Waring, 2006; Deason, Hussey, Ally, & Budson, 2012; Waring, Chong, Wolk, & Budson, 2008), one important question that arose was whether patients with mild AD were capable of altering their response bias. Waring and colleagues (2008) directly examined whether patients with mild AD could shift their response bias if provided with specific instructions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, enhancing patients' reliance on fluency was often found to shift them to a more liberal response bias [5,32]. Although it remains unclear what determines the response bias adopted by AD patients, it seems that, in certain conditions, they are not biased towards "yes" answers or even show conservative criteria [44,53,54]. One such condition, relevant to the current study, is the frequency of verbal stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…A great deal of research has recently been focused on helping patients with mild cognitive impairment or very mild AD use novel techniques to enhance new learning 71,72 . These findings, in addition to work showing that patients can use metacognitive strategies to improve memory performance 73,74 , have led researchers to develop salubrious cognitive rehabilitation programs for these individuals 75 . As part of cognitive rehabilitation to improve memory, many investigators have used mental imagery, which has shown great improvement in healthy older adults 14 .…”
Section: Discussionmentioning
confidence: 98%